Aphorisms by Georg C. Lichtenberg (1742–1799) and André Brie (*1950) on the slide of (meta)language - Sadziński, Witold (Acta Universitatis Lodziensis. Folia Germanica, 2023)
This article confronts aphorisms by two authors who are far apart in the time continuum. What they – the aphorisms – have in common is that they focus on a critical examination of language as a means of communication. The conclusion of the analysis can be summarised as follows. In the first case, we are dealing with a scholar and exact scientist – a university professor of experimental physics in Göttingen in the Age of Enlightenment. The other, on the other hand, is a contemporary politician and active parliamentarian. As one would expect, the former insists on an exact analysis of the means of language and resists imposing limits on it. The other aphorist, on the other hand, is inclined to commit himself to precise linguistic formulations. His expressis verbis credo is rather committed to dialectics and reads: You should not read an aphorism several times in order to understand it once, but read it once in order to understand it several times.